Classical solutions of yang-mills-chern-simons theory in 2+1 dimensions : a quasi-linear superposition / Rosy Teh - Teh, Rosy (Biro Penyelidikan dan Perundingan, Institut Teknologi MARA, 1994)
We pointed out that there exists a critical frequency of oscillation for the vortex-like solution (Teh 1990a) above which the system switches to the fields of an alternating current inside a solenoid. We also show the existence of a non-abelian gauge for which the fields can alternate periodically in space between the abelian fields and another abelian (or non-abelian) fields pointing in a different isospin space direction. The solutions discussed here are real, zero-action Minkowski space configurations.